A Strategic Review on Carbon Quantum Dots for Cancer-Diagnostics and Treatment - Naik, Kaustubh; Chaudhary, Shilpi; Ye, Lei; Parmar, Avanish Singh (Frontiers in Bioengineering and Biotechnology, 2022)
The understanding of the genesis of life-threatening cancer and its invasion calls for urgent development of novel technologies for real-time observations, early diagnosis, and treatment. Quantum dots (QDs) grabbed the spotlight in oncology owing to their excellent photostability, bright fluorescence, high biocompatibility, good electrical and chemical stability with minimum invasiveness. Recently, carbon QDs (CQDs) have become popular over toxic inorganic QDs in the area of bioimaging, biosensing, and drug delivery. Further, CQDs derived from natural sources like biomolecules and medicinal plants have drawn attention because of their one-pot, low-cost and ease of synthesis, along with remarkable tunable optical properties and biocompatibility. This review introduces the synthesis and properties of CQDs derived from natural sources, focusing on the applicability of CQD-based technologies as nano-theranostics for the diagnosis and treatment of cancer. Furthermore, the current issues and future directions for the transformation of CQDs-based nanotechnologies to clinical applications are highlighted.